Demons in the details: demonic discourse and Rabbinic culture in late antique Babylonia - Ronis, Sara (University of California Press, 2022)
Origin stories -- Classification matters -- How to avoid demonic dangers -- Legal demons -- Serving the Rabbinic project -- Exorcising demons.